The Popular Formula of Orson Scott Card's Ender's Game: Exploring the Conventions and Cultural Significance of a Science- Fiction Classic - Mochammad Sulthon Samudra Rizky Zulkarnaen (Fakultas Ilmu Budaya, 2024)
Ender's Game, a science fiction novel by Orson Scott Card, follows the journey of Ender Wiggin, a young boy trained to become a military leader in humanity's war against an alien race known as the Formics. The novel explores themes of leadership, morality, and the psychological toll of warfare, making it a beloved classic since its publication in 1985. This thesis analyzes Ender’s Game using John G. Cawelti’s Popular Formula framework, focusing on how the novel both adheres to and innovates within the science fiction genre. It examines the novel’s narrative structure, character development, and cultural significance, especially in the context of the Cold War era in the United States (1985-1991). The research highlights how Ender’s Game reflects cultural values such as militarism, leadership, and the ethical use of technology, while offering critiques of authoritarianism and the military-industrial complex. Through Cawelti’s theory, the study identifies formulaic elements like the hero’s journey, clear-cut moral universe, and action-driven plot, linking them to the anxieties of Cold War America. It explores how Ender’s Game balances traditional science-fiction tropes with innovative storytelling, resulting in a work that resonates with readers across generations.
Reupload file repositori 02 Mar 2026_Maya
Keywords: Science-Fiction Classic